Marketing Communication Strategy to Increase RA Yasdjanur Bogor Enrollment in 2021/2022 - Aly Aulia; Erwan Sudiwijaya; Salsabila Aulia Putri (Jogjakarta Communication Conference (JCC), 2023)
This study investigates the manner in which educational institutions, specifically schools, implement marketing communication strategies. RA Yasdjanur is an Islamic-based kindergarten that was established in 2005 and has advantages in character building and home visit programs. This study aims to determine the marketing communication strategy to increase RA Yasdjanur Bogor enrollment in 2021/2022. The theoretical framework consists of the marketing communication strategy and marketing communication mix theories. This research approach is qualitative with a descriptive method. By examining the stages of communication and promotional tools implemented via interviews and additional supporting data. The results of this study indicate that RA Yasdjanur uses all elements of the marketing communication mix to increase student enrollment, but the most effective is social media promotion. In addition, RA Yasdjanur executes all phases of developing effective communication to achieve the school's objective of increasing enrollment.